Options for crop establishment techniques in lowland rice cultivation: transplanting vs direct seeding - Islam, Md. Syedul; Ahmad, Desa (Universiti Putra Malaysia, 1999)
Experiments were conducted to determine the field and economic performances of machines and techniques for crop establishment in lowland paddy available in Bangladesh. The work rate of random seeding by hand was found to be approximately 100 times faster than that of hand transplanting. On the other hand, machine seeding was 10 times faster than machine transplanting. The partial budget analysis implied that a shift from manual transplanting to manual seeding incurred a net loss of US$30 per hectare. On the other hand, shifting from machine transplanting to machine seeding, the net loss was found to be US$27 per hectare. The partial budget analyses between mechanised and manual systems for transplanting showed a net benefit of US$13 per hectare. However, in the case of direct seeding, shifting from manual to the mechanised system earned a net benefit of US$53 per hectare. For crop establishment in lowland paddy, shifting from transplanting to seeding practice is not economically attractive to the farmers of Bangladesh at the present level of labour wage. However, shifting from traditional to the mechanised practice for transplanting and seeding operations were found profitable with the minimum uses of 1.8 ha and 0.3 ha respectively.